Employment policies: A methodology approach to the identification of employment opportunities - Luis Palma-Martos; Jose Luis Martin-Navarro (European Regional Science Association (ERSA), 1998)
Unemployment rate in Spain is twice the average unemployment rate in the European Union. The economic literature has identify two main features of spanish unemployment: it is very extremly high and it is persistent. The behaviour of regional unemployment rate presents even more critical situations. For example, Andalusia has an unemployment rate of more than 32%. In this context, the creation of employmnet in traditional economic sectors is not sufficient. New employment opportunities must be discovered and exploted. This paper presents a tentative approach to the identification of employment opportunities in social services with potential posibilities of employment. We present an approach to a macroscopic and strategic public policy. In our oppinion, this policy must follow this steps: 1) Study of the geographical situation of the public service necesities. 2) Identification of potential clients and demand. 3) Definition of social requested services. This macroscopic and strategic analysis constitutes the initial basis of a more deep study to detect employment opportunities in which tratitional markets studies, labour supply and demand, institutional and cultural features will be eessential. Key words: employment opportunities, employment policy, employment deposits
Keywords: 330